Technological diffusion and productivity convergence across European regions: A spatial approach over the period 2000-2015 - Fabio Manca; Giuseppe Piroli (Economics and Econometrics Research Institute (EERI), 2021)
What are the drivers of growth and convergence in productivity at regional level? Differences in the stock of human capital across regions are hypothesized to be the major cause of differences in the speed by which following regions converge and catch-up with the most advanced ones. In addition, we test the role played by R&D expenditures and institutions exploiting a database covering European regions from 1995 to 2015, which includes regional total factor productivity (TFP) computed by the conventional residual approach. We find robust empirical evidence for these hypotheses in terms of both model specifications and sectoral disaggregation.
Keywords: P48; D24; J24; E02; C31; C33; 330; Regional Studies; European Regions; Catching-up; Total Factor Productivity; Human Capital; R&D; Institutions; Spatial Models; Panel Data Models